2023
DOI: 10.3329/bjpt.v30i1.67046
|View full text |Cite
|
Sign up to set email alerts
|

Three new records of Lauraceae for Bangladesh

Abstract: During the floristic explorations conducted in 2022–2023 in different forest areas of the northeast region of Bangladesh, some specimens of the family Lauraceae were collected. Following critical examination, these specimens have been identified as belonging to the species Litsea kurzii, Litsea stocksii, and Litsea variabilis of the family Lauraceae. These species are new to the flora of Bangladesh. A detailed taxonomic description, including data on ecology, distribution, and use, a list of representative spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the last several decades, they have published a significant number of new records as a part of their persistent efforts to discover new plant species from this country. Since the publication of Ahmed et al (2008Ahmed et al ( -2009Ahmed et al ( , 2009 and Siddiqui et al (2007), about 288 new records pertaining to the angiosperms of this country have been made available (e.g., Rahman and Hassan, 2017;Islam and Rahman, 2017;Sourav et al, 2017;Ara and Hassan, 2018;Rahman and Uddin, 2018;Uddin, 2018;Alfasane et al, 2019;Hossain et al, 2020;Sultana and Rahman, 2021;Hossain et al, 2022;Rahman et al, 2022;Sultana et al, 2022;Uddin and Uddin, 2022;Hossain et al, 2023;Rahman et al, 2023). The majority of these new records contain information on the precise locality of the species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last several decades, they have published a significant number of new records as a part of their persistent efforts to discover new plant species from this country. Since the publication of Ahmed et al (2008Ahmed et al ( -2009Ahmed et al ( , 2009 and Siddiqui et al (2007), about 288 new records pertaining to the angiosperms of this country have been made available (e.g., Rahman and Hassan, 2017;Islam and Rahman, 2017;Sourav et al, 2017;Ara and Hassan, 2018;Rahman and Uddin, 2018;Uddin, 2018;Alfasane et al, 2019;Hossain et al, 2020;Sultana and Rahman, 2021;Hossain et al, 2022;Rahman et al, 2022;Sultana et al, 2022;Uddin and Uddin, 2022;Hossain et al, 2023;Rahman et al, 2023). The majority of these new records contain information on the precise locality of the species.…”
Section: Introductionmentioning
confidence: 99%
“…With the addition of these new records to the 3611 Angiosperm species described in the Encyclopedia of Flora and Fauna of Bangladesh EFFB), edited by Ahmed et al (2008Ahmed et al ( -2009Ahmed et al ( , 2009 and Siddiqui et al (2007), the total number of species of this plant group reported from Bangladeshi territory has now risen to 3899 (Hossain et al 2023;Rahman et al 2023). It means the status of at least 1101 (20.16%) species of Angiosperms in this country is unknown and needs to be explored for adding new data and obtaining a better idea of this country's flora, if Khan's (1977) estimation of 5000 species' occurrence in Bangladesh and all new records for this country reported so far after the publication of EFFB are considered.…”
Section: Introductionmentioning
confidence: 99%